Anaerobic membrane bioreactors for wastewater treatment: Novel configurations, fouling control and energy considerations. (July 2019) - Maaz, Muhammad; Yasin, Muhammad; Aslam, Muhammad; Kumar, Gopalakrishnan; Atabani, A.E.; Idrees, Mubbsher; Anjum, Fatima; Jamil, Farrukh; Ahmad, Rizwan; Khan, Asim Laeeq; Lesage, Geoffroy; Heran, Marc; et al.
Graphical abstract: Highlights: Challenges and opportunities of AnMBRs are critically reviewed. Novel configurations of AnMBRs are presented to overcome technology limitations. Energy demand and energy production potential with different AnMBRs are analyzed. Innovative strategies to reduce energy demands and fouling are critically discussed. Future perspectives and key issued required urgent attention are highlighted. Abstract: Water shortage, public health and environmental protection are key motives to treat wastewater. The widespread adoption of wastewater as a resource depends upon development of an energy-efficient technology. Anaerobic membrane bioreactor (AnMBR) technology has gained increasing popularity due to their ability to offset the disadvantages of conventional treatment technologies. However there are several hurdles, yet to climb over, for wider spread and scale-up of the technology. This paper reviews fundamental aspects of anaerobic digestion of wastewater, and identifies the challenges and opportunities to the further development of AnMBRs. Membrane fouling and its implications are discussed, and strategies to control membrane fouling are proposed. Novel AnMBR configurations are discussed as an integrated approach to overcome technology limitations. Energy demand and recovery in AnMBRs is analyzed. Finally key issues that require urgent attention to facilitate global penetration of AnMBR technology are highlighted.